2005
DOI: 10.1590/s0004-282x2005000600008
|View full text |Cite
|
Sign up to set email alerts
|

Facial sensory symptoms in medullary infarcts

Abstract: Our results show a correlation between medial extension of LMIs and presence of contralateral facial sensory symptoms.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2008
2008
2014
2014

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 13 publications
(9 reference statements)
0
1
0
Order By: Relevance
“…Kim showed that patients with contralateral trigeminal involvement were more likely to have a ventrally located lesion in the brain stem. Conforto et al 10 investigated the correlation between facial sensory abnormalities and lesion topography in eight patients with LMI, and their results showed that contralateral facial sensory abnormalities are related to medial extension of the infarct. In conclusion, sparing the spinal trigeminal tract and its nucleus while disrupting the ventral trigeminothalamic tract accounts for this atypical presentation.…”
Section: Discussionmentioning
confidence: 99%
“…Kim showed that patients with contralateral trigeminal involvement were more likely to have a ventrally located lesion in the brain stem. Conforto et al 10 investigated the correlation between facial sensory abnormalities and lesion topography in eight patients with LMI, and their results showed that contralateral facial sensory abnormalities are related to medial extension of the infarct. In conclusion, sparing the spinal trigeminal tract and its nucleus while disrupting the ventral trigeminothalamic tract accounts for this atypical presentation.…”
Section: Discussionmentioning
confidence: 99%